1998
DOI: 10.1016/s0014-5793(98)01002-3
|View full text |Cite
|
Sign up to set email alerts
|

Human serum, cysteine and histidine inhibit the oxidation of low density lipoprotein less at acidic pH

Abstract: Low concentrations of serum or interstitial fluid have been shown to inhibit the oxidation of low density lipoprotein (LDL) catalysed by copper or iron, and may therefore protect against the development of atherosclerosis. As atherosclerotic lesions may have an acidic extracellular pH, we have investigated the effect of pH on the inhibition of LDL oxidation by serum and certain components of serum. Human serum (0.5%, v/v), lipoprotein-deficient human serum at an equivalent concentration and the amino acids L-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…The enzyme reaction in the tube, which contains NADPH, reduced glutathione, sodium azide, and glutathione reductase, was initiated by addition of hydrogen peroxide, and the change in absorbance at 340 nm was monitored by a spectrophotometer. Activity was given as units per gram of hemoglobin in erythrocyte samples (Patterson and Leacke 1998).…”
Section: Gpx Activitymentioning
confidence: 99%
“…The enzyme reaction in the tube, which contains NADPH, reduced glutathione, sodium azide, and glutathione reductase, was initiated by addition of hydrogen peroxide, and the change in absorbance at 340 nm was monitored by a spectrophotometer. Activity was given as units per gram of hemoglobin in erythrocyte samples (Patterson and Leacke 1998).…”
Section: Gpx Activitymentioning
confidence: 99%
“…A possible role of the highly reactive oxygen free radicals in the pathogenesis of parasitic infections has been an active area of research over the past ten years (Biswas et al, 1997;Erel et al, 1997;Oliveira and Cechini, 2002). The main targets of free oxygen radical activity are polyunsaturated fatty acids (PUFAs) in membrane phospholipids, the modification of which result in disorganization of the cellular framework and function (Patterson and Leacke, 1998).…”
mentioning
confidence: 99%
“…A protein assay, conducted as described above, showed that between 98-100% (n ϭ 3) of the apolipoprotein was removed. Previous work (23) has shown an absence of lipoprotein bands after electrophoresis of similarly treated serum on agarose gels, and minimal removal of other protein from the serum.…”
Section: Preparation Of Lipid-deficient Plasmamentioning
confidence: 87%